2020 IEEE Wireless Communications and Networking Conference (WCNC) 2020
DOI: 10.1109/wcnc45663.2020.9120537
|View full text |Cite
|
Sign up to set email alerts
|

SEdroid: A Robust Android Malware Detector using Selective Ensemble Learning

Abstract: For the dramatic increase of Android malware and low efficiency of manual check process, deep learning methods started to be an auxiliary means for Android malware detection these years. However, these models are highly dependent on the quality of datasets, and perform unsatisfactory results when the quality of training data is not good enough. In the real world, the quality of datasets without manually check cannot be guaranteed, even Google Play may contain malicious applications, which will cause the traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Except that, Qiu et al [131] divide malware into high impact and low impact based on impact ground truth of cyber-security or privacy impact, and propose a framework to predict the impact of Android malware. To maximize the detection performance, five studies apply various search techniques to explore the optimum parameters and DNN structures, including grid search [22,123], Tree-structured Parzen Estimator (TPE) [122], and genetic algorithms [105,170]. However, excellent detection performance doesn't necessarily mean promising effectiveness and reliability, because these methods merely provide classification results, which is not enough.…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Except that, Qiu et al [131] divide malware into high impact and low impact based on impact ground truth of cyber-security or privacy impact, and propose a framework to predict the impact of Android malware. To maximize the detection performance, five studies apply various search techniques to explore the optimum parameters and DNN structures, including grid search [22,123], Tree-structured Parzen Estimator (TPE) [122], and genetic algorithms [105,170]. However, excellent detection performance doesn't necessarily mean promising effectiveness and reliability, because these methods merely provide classification results, which is not enough.…”
Section: Results Analysismentioning
confidence: 99%
“…OPEN ISSUE Verifying the existence of certain categorical characteristics of Android applications, such as permissions/API calls by static analysis or certain malicious behaviors by dynamic analysis, is widely used to construct feature vectors [5,7,18,22,29,40,44,45,47,57,67,68,74,78,90,92,101,105,109,111,113,128,131,143,145,156,157,166,170,172,174,179,185,197,198,203,209]. The researchers usually build a look-up table to list all the potential features, based on prior knowledge or feature selection approaches, and a fixed-size binary feature vector is created to represent the feature information for each application.…”
Section: Rq21 How Features Are Processed For Model Training?mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, to be efficiently deployed to production-quality scenarios, the bio-inspired methods require facing several problems, such as solving the imbalance of a dataset [125], tuning the configurations of neural network models [126], as well as finding the optimal combination of parameters while avoiding the problem of falling into local optimal solution [127]. However, GA algorithms demonstrated their capability for obtaining a strong generalization ability and robustness by finding the best learner group for ensemble models [128]. As a paradigmatic example of the use of bio-inspired approaches, in [129] the authors proposed a novel way for detecting code hidden with three commonly used steganographic tools via an Artificial Immune System.…”
Section: E Bio-inspired and Other Detection Methodsmentioning
confidence: 99%
“…A. Meimandi et al [15] showed a performance improvement by combining genetic algorithm and the simulated annealing with classification algorithm. J. Wang et al [16] introduced SEdroid, an Android malware detector based on a genetic algorithm and ensemble learning. L. Wang et al [17] introduced a new algorithm based on the genetic algorithm for applications of Android malware classification problems.…”
Section: Introductionmentioning
confidence: 99%